2021
DOI: 10.1007/s10517-021-05236-x
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Syncytial Knots and VEGF Expression in Placental Villi in Parturient Woman with COVID-19 Depends on the Disease Severity

Abstract: A comparative morphological study was carried out to analyze the number of syncytial knots and VEGF expression in placental villi in parturient women with COVID-19 categorized by the disease severity. The number of syncytial knots was assessed on specimens stained with hematoxylin and eosin. VEGF expression was determined by immunohistochemical analysis in syncytiotrophoblast and villous endothelial cells. Morphological study of the placenta tissue of parturient women with COVID-19 showed increased numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
(16 reference statements)
0
17
0
1
Order By: Relevance
“…Syncytial knots reflect villous maturity when increased and are regarded as a placental response to trophoblastic ischaemia/underperfusion or maternal hypoxia, classically seen in pre-eclampsia [ 37 , 38 , 39 ] and some maternal bacterial infections [ 28 , 31 , 40 , 41 ]. Shchegolev et al [ 42 ] revealed that the number of syncytial knots in placental villi depended on COVID-19 disease severity, with a corresponding increase in VEGF immunoexpression in the syncytiotrophoblasts and villous endotheliocytes. Comparably, we detected a higher rate of syncytial knot formation in the symptomatic and active COVID-19 groups than in the asymptomatic and resolved counterparts; however, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Syncytial knots reflect villous maturity when increased and are regarded as a placental response to trophoblastic ischaemia/underperfusion or maternal hypoxia, classically seen in pre-eclampsia [ 37 , 38 , 39 ] and some maternal bacterial infections [ 28 , 31 , 40 , 41 ]. Shchegolev et al [ 42 ] revealed that the number of syncytial knots in placental villi depended on COVID-19 disease severity, with a corresponding increase in VEGF immunoexpression in the syncytiotrophoblasts and villous endotheliocytes. Comparably, we detected a higher rate of syncytial knot formation in the symptomatic and active COVID-19 groups than in the asymptomatic and resolved counterparts; however, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we revealed an increase in the specific area of the syncytiotrophoblast that reflects the state of the maternal compartment of the placental blood circulation. This increase in the syncytiotrophoblast area, along with the increase in the number of syncytial knots and bridges in the terminal villi of the placenta in parturient women with COVID-19 [4], indicates the presence of preplacental hypoxia. In our opinion, the latter is the main cause of circulatory disorders of the fetal compartment of the placenta, namely, the increase in the number of capillaries in the placental villi which was revealed in the patients with COVID-19 participating in our study.…”
Section: Resultsmentioning
confidence: 97%
“…Abnormal angiogenesis is frequently observed in placental disorders and infections ( 4446 ). Indeed, a recent study has reported increased levels of VEGF in placental villi by immunohistochemistry staining on COVID-19 samples, which is a feature of hypoxia and associated with preeclampsia ( 47 ). We asked whether SARS-CoV-2 infection would affect the angiogenesis pathway and what was the underlying molecular mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Vasoconstriction, resulting from the suppression of RAS, has been demonstrated in both preeclampsia and SARS-CoV-2 infection ( 5, 72, 75 ). In conjunction with alteration of RAS, changes in expression and imbalance of angiogenic mediators, associated with SARS-CoV-2 infection, result in systemic endothelial dysfunction and the clinical syndrome of preeclampsia ( 5, 47, 76 ). Previous studies have shown endothelial damage, together with overexpression of proangiogenic factors, such as VEGF, basic fibroblast growth factor (FGF-2), and placental growth factors (PlGF) in the plasma or lung biopsies of COVID-19 patients ( 77 ).…”
Section: Discussionmentioning
confidence: 99%